Introducing morphology - Lieber, Rochelle, 1954- (Cambridge introductions to language and linguistics, 2019)
"Morphology is the study of how words are put together. A lively introduction to the subject, this textbook is intended for undergraduates with relatively little background in linguistics. Providing data from a wide variety of languages, it includes hands-on activities such as 'challenge boxes', designed to encourage students to gather their own data and analyze it, work with data on websites, perform simple experiments, and discuss topics with each other. There is also an extensive introduction to the terms and concepts necessary for analyzing words. Topics such as the mental lexicon, derivation, compounding, inflection, morphological typology, productivity, and the interface of morphology with syntax and phonology expose students to the whole scope of the field. Unlike other textbooks it anticipates the question 'Is it a real word?' and tackles it head on by looking at the distinction between dictionaries and the mental lexicon. This second edition has been thoroughly updated, including new examples and exercises as well as a detailed introduction to using linguistic corpora to find and analyze morphological data"--